Diametrika Paradigma Penelitian Ilmu Ekonomi - Leksono, Sonny (Jurnal Aplikasi Manajemen, 2008)
In general, if the science is distinguished into two kinds - the main branch - is that natural sciences and social sciences, so economical science is included into social sciences domain. Economical research relating with efficiency and effectiveness problems for something - goods commodity -- may loan natural science owned method, procedure, and approach; but, the economical research relating with human being as economical agent, so the method, approach and procedure - exactly and precisely - is in accordance with social science paradigm. So, economical science research is faced with two kinds of paradigm choice (or - conflict), is that relying on positivism philosophy ideology/paradigm and nonpositivism philosophy ideology. Positivism ideology in the research develops to he research with quantitative paradigm, if it is implemented in economy science research obtained is to examine the truth or apply a theory: In methodology, positivism uses empirical-analytical method, deduction logic, survey research technique, statistic (included non parametric or descriptive), and various quantitative study technique and it is designed with calculative models. In turn, the truth non-positivism philosophy is based on idea essence (in accordance with object essence) and its truth is holistic in nature. Understanding the fact and data in non-positivism philosophy also has coverage beside empirical sensual (phenomena) in nature is highly track what is behind the empirical sensual (phenomena). Non-positivism philosophy finds the meaning on empirical idea in the research that develops to be research in qualitative paradigm. In ontological way, positivism is weak in the matter of building theory concept. On other word, there is no contribution in building the theory: Furthermore, the science (social and/or economy) that is developed with positivism-based methodology becomes have less its theoretical concepiualization, und there is no basic new theories evolve. Positivism epistemology requires generalization and separation between observed subjects with a researcher as its instrument so that there is objectivity. The question is how to get the theory without involvement of researcher subject. Axiological aspect in science philosophy is striving to answer the question: "for what the knowledge or science is used? It is stated that the science must be used for human being benefit. Whereas, positivism axiology requires the free-value allocation.